2016
DOI: 10.1080/10410236.2016.1196415
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Public’s Intentions to Purchase and to Persuade Others to Purchase Antibiotic-Free Meat

Abstract: Extending the effectiveness of media-based campaigns into interpersonal networks has been a long concern for studies on persuasive messages, yet there is much to understand about why people attempt to persuade others to engage in health-related behaviors. This study investigated two alternative predictors of interpersonal persuasion: psychosocial determinants of behavior and homophily. We used the integrated model of behavior (IMB) to predict consumers’ intentions to purchase antibiotic-free meat, and extended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…A high-knowledge consumer does not necessarily know specific information about antibiotic regimes and their role in animal production. Indeed, the components of antibiotic use that consumers were asked about in these studies were very basic, such as if they know what antibiotics are [ 41 , 42 ]. Instead, “knowledge” can mean that a consumer understands the rules of thumb that labels provide, or has a general understanding of what antibiotics are, and how they are used in our food systems.…”
Section: Discussionmentioning
confidence: 99%
“…A high-knowledge consumer does not necessarily know specific information about antibiotic regimes and their role in animal production. Indeed, the components of antibiotic use that consumers were asked about in these studies were very basic, such as if they know what antibiotics are [ 41 , 42 ]. Instead, “knowledge” can mean that a consumer understands the rules of thumb that labels provide, or has a general understanding of what antibiotics are, and how they are used in our food systems.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to consumers' purchase intentions, various other studies have similarly found that such perceptions determine purchasing behaviour (Lobb et al, 2007;Stefani et al, 2008;Kapuge, 2016;Smith et al, 2017). Stefani et al (2008) found that risk perception was an important determinant of attitude and related to intention to purchase chicken, and similarly, Kapuge (2016) identified that there was a significant impact of health consciousness on purchase intention of organic food among Sri Lankan consumers.…”
Section: Factors Influencing Willingness To Buy 'Raised Without Antib...mentioning
confidence: 92%
“…Stefani et al (2008) found that risk perception was an important determinant of attitude and related to intention to purchase chicken, and similarly, Kapuge (2016) identified that there was a significant impact of health consciousness on purchase intention of organic food among Sri Lankan consumers. In relation to antibiotic research specifically, Smith et al (2017) uncovered that those who had higher concerns for AMR (i.e., personal risk perception) likely have limited knowledge, which may have prompted them to report negative views towards antimicrobial use in food animal production and, consequently, about intending to purchase antibiotic free meat.…”
Section: Factors Influencing Willingness To Buy 'Raised Without Antib...mentioning
confidence: 99%
See 1 more Smart Citation
“…Now, we move to the last but critical mechanism regarding the mutual adjustment of the voluntary adoption of public health measures or subjective health perceived by both connected citizens. In a context in which individuals with distinct levels of countermeasures adopted for health protection or self-reported health are linked to each other for health communication during this pandemic, each citizen's acceptance of public health preventive measures or subjective health may be adapted to and influenced by those of their risk communication partners [36][37][38]. Through a social contagion or reciprocal influence process mediated by repeated connections for discussions on health risk over time among them, citizens' individual adoption of public health preventive measures or self-evaluation of health may spread through the previously established ties for risk discourses and then lead to the convergence of these properties toward a specific level [21,36].…”
Section: Associational Mechanisms (The Mutual Adaption/influence Effect In the Coevolutionary Process)mentioning
confidence: 99%